The Florida Bull Test 2009–2010 - G.Cliff Lamb (EDIS)
AN251, a 6-page fact sheet by G. Cliff Lamb, reports on this performance test and breeding soundness evaluation conducted in 2009-2010 — procedures, rules and regulations, results, and sale summary. Includes 2010-2011 test dates and a table of individual animal performance. Published by the UF Department of Animal Sciences, October 2010.